2019
DOI: 10.1021/acsphotonics.9b00466
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Carrier Density Gradients along Axially Doped Silicon Nanowires Using Infrared Nanoscopy

Abstract: Doped semiconductor nanostructures are interesting for the fabrication of nanoscale electronic and photonic devices. Here, we use scattering-type scanning near-field optical microscopy (s-SNOM) to characterize axial carrier density gradients in phosphorus-doped silicon nanowires. We quantitatively determine the carrier density and length of the doped segment as well as the functional form of the charge carrier gradient in the transition region between doped and nominally undoped segments. These measurements ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Additionally, even ultra-thin surface layers with a thickness below 5 nm can significantly influence the s-SNOM contrast beyond mere dielectric screening if they exhibit resonant behavior in the spectral region of interest. This exceptional surface sensitivity was previously shown for phonon resonances of the native oxide on doped silicon nanowires, [29] and therefore has to be implemented for a quantitative analysis.…”
Section: Influence Of the Lao Thickness On The Near-field Responsementioning
confidence: 68%
“…Additionally, even ultra-thin surface layers with a thickness below 5 nm can significantly influence the s-SNOM contrast beyond mere dielectric screening if they exhibit resonant behavior in the spectral region of interest. This exceptional surface sensitivity was previously shown for phonon resonances of the native oxide on doped silicon nanowires, [29] and therefore has to be implemented for a quantitative analysis.…”
Section: Influence Of the Lao Thickness On The Near-field Responsementioning
confidence: 68%
“…This so far unknown aspect might offer additional adjustment possibilities for future material engineering. Furthermore, it was shown that quantitative investigations of vertical material compositions are possible using s-SNOM measurements (60,61). Comparing multilayered finite dipole models with experimental tomographic s-SNOM data will allow to study, e.g., the local hydrogenation depth in our Mg/ MgH 2 films.…”
Section: Resultsmentioning
confidence: 99%
“…[ 31,32 ] The IR amplitude and phase spectra of the InAs ZB nanowire in Figure 3a exhibit a broad plasmonic response. A Drude model [ 21,33–37 ] is applied to successfully fit the spectral data of the InAs ZB nanowire whose electron concentration is 2.37 × 10 19 cm −3 (solid lines in Figure 3a). Figure 3b shows the IR amplitude and phase spectra of an InAs ribbon whose electron concentration is 1.92 × 10 19 cm −3 .…”
Section: Figurementioning
confidence: 99%